Interleukin‐1 as a pharmacological target in acute brain injury. Issue 12 (14th July 2015) - Brough, David; Rothwell, Nancy J.; Allan, Stuart M.
Abstract : New Findings: What is the topic of this review ? This review discusses the latest findings on the contribution of inflammation to brain injury, how inflammation is a therapeutic target, and details of recent and forthcoming clinical studies. What advances does it highlight? Here we highlight recent advances on the role and regulation of inflammasomes, and the latest clinical progress in targeting inflammation. Acute brain injury is one of the leading causes of mortality and disability worldwide. Despite this, treatments for acute brain injuries are limited, and there remains a massive unmet clinical need. Inflammation has emerged as a major contributor to non‐communicable diseases, and there is now substantial and growing evidence that inflammation, driven by the cytokine interleukin‐1 (IL‐1), worsens acute brain injury. Interleukin‐1 is regulated by large, multimolecular complexes called inflammasomes. Here, we discuss the latest research on the regulation of inflammasomes and IL‐1 in the brain, preclinical efforts to establish the IL‐1 system as a therapeutic target, and the promise of recent and future clinical studies on blocking the action of IL‐1 for the treatment of brain injury. Abstract :